IMPLEMENTASI KEBIJAKAN PENDIDIKAN SEKOLAH MARGINAL DI DESA SIMPANG GAUNG KECAMATAN GAUNG KABUPATEN INDRAGIRI HILIR - HAIRIANI. A HAIRIANI. A; AZHAR AZHAR; FAKHRI RAS (Universitas Riau, 2017)
The aim of this research is how the implementation of education policy ofsentosa marginal school. With subfokus viz: (1) Targets in the application of education policyimplementation of Marginal School in Dusun Sentosa Desa Simpang Gaung Kecamatan GaungKabupaten Indragiri Hilir Provinsi Riau (2) the implementation of the education system ofMarginal School in Dusun Sentosa Desa Simpang Gaung Kecamatan Gaung Kabupaten IndragiriHilir Provinsi Riau (3) availability of facilities and infrastructure to support the provision ofMarginal School education in Dusun Sentosa Desa Simpang Gaung Kecamatan GaungKabupaten Indragiri Hilir Provinsis Riau (4) Learning process of Marginal School in DusunSentosa Desa Simpang Gaung Kecamatan Gaung Kabupaten Indragiri Hilir Provinsi Riau.This research used Qualitative Descriptive collected from respondents with data collectionthrough documentation, observation anddeep interview. Furthermore, data analysis through datareduction, data display along with conclusion and verification.The result of the research showsthat: (1) Targets in the application of education policy implementation of Marginal School are inaccordance with educational policy of marginal school that isthe marginalized children of DusunSentosa (2) the implementation of the education system in Sentosa marginal school includes:(a) Curriculum that is used in SMP Marginal following the holding schoolthat is school-basedcurriculum (KTSP) (b) the number of the teacherare 4 person and living close to SentosaMarginal School (c)the budgeting sourced from BOS fund andmanaged by the holding school(3) the availability of facilities and infrastructure to support the provision of Marginal Schooleducation is still very limited, SMP Marginal does not have its own building, the learning tool isonly the teachers textbook. SMP Marginal Sentosa utilizing the existing infrastructure, thingsthat are needed such as chalk directly requested to the holding school (4) the learning processof Sentosa Marginal School are more conditioned to the situation of students as well as facilitiesand infrastructure.